The competition numbers of Johnson graphs with diameter four - Kijung Kim (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2017)
In 2010, Kim, Park and Sano studied the competition numbers of Johnson graphs. They gave the competition numbers of J(n,2) and J(n,3).In this note, we consider the competition number of J(n,4).